Disabled people in housing estates - Rawski, Kamil (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2019)
Much attention is paid to adapting public buildings or transport for the disabled. Not much, however, to spaces where the journey to a given destination begins. The path that has to be walked from the apartment until reaching public transport can significantly hinder the lives of people with reduced mobility. A housing estate is also a place where people spend a large part of their free time. Therefore, in order not to exclude disabled people from social life, designing such places in an accessible way is extremely important. And exactly this issue was raised in this article.